A FEEDBACK ON THE WORD AND ITS MEANINGS IN GERMAN AND UZBEK LANGUAGES (TAMADDUN NURI JURNALI, 2025)
In this article, words and their semantic features are studied through a comparison of German and Uzbek. The characteristics of meaning, content, and reference of words, along with their differences, are revealed. The effects of meanings on human consciousness, whether intrinsic, composite, or associative, are also analyzed.